Korupsi Berbasis Tradisi: Akar Kultural Penyimpangan Kekuasaan di Indonesia - Achmad Zainuri (Refleksi: Jurnal Kajian Agama dan Filsafat, 2005)
Corruption in this country has spread to all sectors like an octopus. This deviation not only infiltrates areas that have been perceived by the public as nests of corruption but also delves into corridors of institutions that were previously unimaginable to have corruption. One by one, financial scandals in various state institutions have been uncovered. Even the General Election Commission (KPU), filled with democracy activists, academics, and professors, is not immune to the corruption epidemic. In the Department of Religion (Depag), corruption cases have even implicated its former top official as a suspect. This article attempts to uncover the roots of tradition and culture behind these deviations.